The Neglected Role of Patients in Promoting Patient Safety - Mohanna Rajabi (Shiraz University of Medical Sciences, 2024)
Providing safe and high-quality care has always been one of the main challenges for healthcare organizations and a fundamental concern for health systems, patients, and societies worldwide.